2017
DOI: 10.1021/acssuschemeng.6b03003
|View full text |Cite
|
Sign up to set email alerts
|

Copper Sulfide Nanoparticle/Cellulose Composite Paper: Room-Temperature Green Fabrication for NIR Laser-Inducible Ablation of Pathogenic Microorganisms

Abstract: This work reports a new type of near-infrared (NIR) laser-inducible antimicrobial composite paper based on copper sulfide nanoparticles (CuS NPs). For the first time, a smart and green method to prepare CuS NPs was developed by taking advantage of the copper−amine complex as the copper source and sodium sulfide as the sulfur source at room temperature, in which a biopolymer xylan was used as the growth template and stabilizing agent. The obtained xylan/CuS NPs composites (CuS@Xylan NPs) were spherical and stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…However, prepared CuS NPs in solid form have been reported using different sulfide sources viz. sodium sulfide (Huang et al 2017;Riyaz et al 2016;Ayodhya et al 2016;Shamsipur et al 2013;Castillon-Barraza et al 2011;Ding et al 2010), sodium thiosulfate (Nafees et al 2015;Kundu and Pradhan 2013; Percent radial growth inhibition ¼ Radial growth of fungal colony in control À Radial growth of fungal colony in treatment Radial growth of fungal colony in control  100 With the increase in level of capping the size reduces and in turn, the k max value get relatively blue shifted (Rani 2016), which is the most probable explanation for the altered optical properties of nanoparticles when capped.…”
Section: Resultsmentioning
confidence: 99%
“…However, prepared CuS NPs in solid form have been reported using different sulfide sources viz. sodium sulfide (Huang et al 2017;Riyaz et al 2016;Ayodhya et al 2016;Shamsipur et al 2013;Castillon-Barraza et al 2011;Ding et al 2010), sodium thiosulfate (Nafees et al 2015;Kundu and Pradhan 2013; Percent radial growth inhibition ¼ Radial growth of fungal colony in control À Radial growth of fungal colony in treatment Radial growth of fungal colony in control  100 With the increase in level of capping the size reduces and in turn, the k max value get relatively blue shifted (Rani 2016), which is the most probable explanation for the altered optical properties of nanoparticles when capped.…”
Section: Resultsmentioning
confidence: 99%
“…2). Huang et al [28] observed that different microbial cell structures may be an important reason for the different antimicrobial effects. Unlike the other microorganisms, the fungus A. niger has a denser cell wall; moreover, and it is very difficult to inhibit its fungal spores.…”
Section: Fungal Growthmentioning
confidence: 99%
“…In this work, we report a Cu 2-x S NRs-PVA gel approach, comprising photothermal generators (Cu 2-x S NRs) [ 23 ] and a floatable PVA supporting base [ 24 ]. Copper chalcogenide semiconductor nanocrystals were considered as the most promising green and sustainable photothermal agents, due to their low cost, high photo-stability, and high absorption cross-section, which could efficiently convert solar energy into heat [ 25 , 26 , 27 , 28 ]. The hierarchical structure in PVA hydrogel, which consists of big channels, capillary channels, and micro holes, can efficiently replenish and transport water into confined areas for localized heating [ 22 ].…”
Section: Introductionmentioning
confidence: 99%